Plasma TIMP1 level is a prognostic factor in patients with liver metastases - Bunatova, Karin; Pesta, Martin; Kulda, Vlastimil; Topolcan, Ondrej; Vrzalova, Jindra; Sutnar, Alan; Treska, Vladislav; Pecen, Ladislav; Liska, Vaclav (Anticancer research, 2012)
UNLABELLED: TIMP1 (tissue inhibitor of metalloproteinases 1) regulates extracellular matrix turnover and also promotes cell growth and has anti-apoptotic activity, which promotes malignant processes in tumor tissue. The aim of our study was to evaluate the relation of plasma TIMP1 protein levels with prognosis in patients with liver metastases, with particular regard to possible early-prediction of recurrence of the disease. PATIENTS AND METHODS: We studied a group of 87 patients with metastatic liver disease (mostly from colorectal cancer) who underwent surgery for liver metastases, and assessed their preoperative plasma TIMP1 levels. These levels were evaluated according to prognosis. Furthermore, we measured plasma TIMP1 in the post-operative period and tried to relate the changes with the diagnosis of relapse. RESULTS: We found preoperative plasma TIMP1 levels to be related to overall survival in the group of all patients with metastatic liver disease (p=0.0047), with a higher level being associated with an adverse outcome; the cut-off value was set at 165 ng/ml. This applied to all patients, regardless of the type of surgery. Assessment of the post-operative dynamics of TIMP1 was not found to be statistically significant to indicate disease recurrence. CONCLUSION: We found there to be a relationship between higher plasma levels of TIMP1 and an adverse prognosis in patients with liver metastases. The assessment of plasma TIMP1 levels could help the detection of patients with worse outcome.
Keywords: nádory jater; Humans; lidé středního věku; Biomarkers, Tumor; Female; tkáňový inhibitor metaloproteinasy 1; Aged; dospělí; senioři; lidé; Liver Neoplasms; nádorové biomarkery; Adult; ženské pohlaví; kolorektální nádory; Male; Middle Aged; Tissue Inhibitor of Metalloproteinase-1; prognóza; Aged, 80 and over; senioři nad 80 let; lokální recidiva nádoru; mužské pohlaví; Neoplasm Recurrence, Local; Prognosis; Colorectal Neoplasms